Intracapsular and para- articular chondroma of knee - Samardziski, Milan (Radiology and oncology (Ljubljana), 2006)
Background. Intracapsular and para-articular chondroma is a rare variant of the extraskeletal chondromas. It arises from the capsule and/or the para-articular connective tissue of the large joints (mostly the knee) and is a result of cartilaginous metaplasia. In course of time these tumors ossify and this is where their second name comes from: Para-articular osteochondromas. According to Jaffe, not dependent on the degree of ossification of this tumor, there is one single entity in question. Cases report. We report four new cases of para-articulnr chondroma of the knee. On physical examination there was slow growing solid mass in the knee and moderate pain, the radiological findings and CT scan show soft-tissue mass with variable amount of ossification, and on histological examination the presence of mature hyaline and connective cartilage was confirmed in all of the cases. Conclusions. The diagnosis of these benign tumors is made with correlation of clinical, radiological and histological features. The treatmentof choice is surgical excision in toto.
Keywords: Chondroma; Diagnosis; diagnostika; Hondrom; hondromi; Knee Joint; Kolenski sklep; novotvorbe; sklepi; Therapy; tumor